2017
DOI: 10.1017/s0031182017000713
|View full text |Cite
|
Sign up to set email alerts
|

The use ofEscherichia colitotal antigens as a complementary approach to address seropositivity toLeishmaniaantigens in canine leishmaniosis

Abstract: S U M M A R YCanine leishmaniosis (CanL) is a major veterinary concern and a public health issue. Serological data are essential for disease management. Several antigens used in serological assays have specificity related problems preventing relevant seropositivity values establishment. Herein we report significant seropositivity level disparity in a study cohort with 384 dogs from eight countries, for antigens traditionally used in CanL -soluble promastigote Leishmania antigens (SPLA) and K39 recombinant prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…It should be a cause for concern that tests and antigens that are capable of discriminating diseased animals from healthy animals with more than 90% sensitivity and specificity originated such a high percentage of inconclusive serology 8 . Similar discrepancies between antigens (SPLA and rK39) were reported in the context of non-endemic animals 6 . In fact, complex antigens like SPLA can be associated with cross-reactivity 12,13 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It should be a cause for concern that tests and antigens that are capable of discriminating diseased animals from healthy animals with more than 90% sensitivity and specificity originated such a high percentage of inconclusive serology 8 . Similar discrepancies between antigens (SPLA and rK39) were reported in the context of non-endemic animals 6 . In fact, complex antigens like SPLA can be associated with cross-reactivity 12,13 .…”
Section: Discussionsupporting
confidence: 74%
“…Still, comparative studies of serological performance in unbiased clinically suspect animals are lacking. The performance of these tests in field conditions must be addressed, particularly after reports of reduced predictive value of simple serological tests in serological surveys 6 . In this context, we evaluated the consistency of serological evaluation in a group of 82 CanL suspect dogs in Portugal.…”
mentioning
confidence: 99%
“…Considering this scenario, a different approach was tested. We had already reported that the relationship between the seropositivity to rK39 and SPLA presented a pattern that could be predictive of disease associated seropositivity (27), this was once again confirmed in the context of vaccination (Figure 3). In fact, by performing the ratios between the four antigens and SPLA (rK39/SPLA, rK28/SPLA, Lic TXNPx/SPLA, rKDDR/SPLA) and respective ROC curves, we could for the first time distinguish the V- (vaccinated healthy animals) from the other groups studied (V+, C-, and C+).…”
Section: Discussionsupporting
confidence: 65%
“…The proposed score system was used as described by Lima et al [ 24 ] with minor modifications. Optical densities of all samples were screened for seroreactivity using a threshold of 0.014.…”
Section: Methodsmentioning
confidence: 99%
“…The level of antigen-dependent serological reporting is a concern and should be clarified for better integration of serological data in epidemiological settings. To address this question, we evaluated the potential of six different Leishmania -specific antigens: soluble promastigote Leishmania antigen (SPLA), recombinant antigens (LicTXNPx, rK39, rK28, and rKDDR), a mixture of recombinant antigens (LAM) [ 20 ] in conjunction with a non-related antigen, Escherichia coli soluble antigens (SECA) [ 24 ]. Crude promastigote antigens, the SPLA, have been described as highly sensitive for subclinical and clinical infections, but with a lower specificity [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%